Editorial on the article entitled “the impact of intimal tear location and partial false lumen thrombosis in acute type b aortic dissection” - Choo, Suk Jung; Kim, Joon Bum (Journal of Thoracic Disease; Vol 8, No 10 (October 01, 2016): Journal of Thoracic Disease, 2016)
The experimental study analyzing the most likely clinical scenarios in acute type B aortic dissection (ATBAD) with regards to the false lumen (FL) thrombus status by Girish et al. (1) provides valuable information and new insights regarding the prognostic implications and mechanisms of partial FL thrombus formation. While medical therapy remains the treatment of choice for non-complicated ATBAD with early survival rates reaching 90%, surgery and increasingly, thoracic endovascular aortic repair (TEVAR) options remain reserved for urgent life threatening complications such as aortic rupture, enlarging aneurysms, and or evolving organ malperfusion (2,3). Despite the favorable outcomes with medical treatment however, the intermediate to late survival remains concerning with 3 years post discharge mortality rate approximating 25% during the chronic phase (4). Studies to identify risk factors for poorer outcome in ATBAD showed completely patent FLs to be associated with higher rupture and mortality rates than completely thrombosed FLs (5-7). A more recent IRAD study suggested a third entity, partially thrombosed FL to be a significant predictor of increased mortality after ATBAD with all-cause mortality being greater by a factor of 2.7 compared to complete thrombosis (8). Partial FL thrombus formation with a proximal entry and distal tear occlusion was postulated to create a situation analogous to intra-aneurysmal pressure elevation occurring with incomplete endovascular stent graft exclusion. It was shown experimentally that in the presence of an endoleak, a linear correlation occurred between increasing endoleak size and sac pressure (9).